Wanda's Woes - Ann Smith; Daniel C. Stein (Association of American Medical Colleges, 2010)
Abstract Introduction This case study was developed to support learning of infectious disease concepts in a general microbiology course. Students will consider the characteristics of various species of streptococci (pathogenic and nonpathogenic) as they follow the story of the infant Frederica exhibiting various disease conditions. This case was developed to support student learning of infectious disease concepts in a sophomore-level general microbiology course. Methods In this case, students consider the characteristics of various species of streptococci as they follow the story of the infant Frederica with disease conditions of group B streptococcal infection, otitis media, pneumonia, and flesh-eating disease. The case follows an interrupted-case format. Results This case has been used in the general microbiology course at the University of Maryland for 5 years. Four different instructors have elected to use the case and associated questions. Over 5 years, approximately 1,200 students have participated in learning host pathogen interactions concepts via this case study. Instructors report that the case engages students in discussion and consideration of important concepts related to host pathogen interactions, the infectious disease process, and the use of antibiotics as treatment for infectious disease where development of resistance is an issue. Students have commented that the case is interesting and feels realistic. Students identify with the story of the case via their personal circumstances and/or interest in careers in medicine and nursing. Discussion In our course, we use an online course management system to deliver the case to the students. For a very large class, we have found the use of technology to be very helpful. However, the case could be presented without technology, using handouts and collecting written responses on paper instead.